Prognostic value of GLUT-1 expression in oral squamous cell carcinoma: A prisma-compliant meta-analysis. Issue 45 (November 2016) - Li, Chen-Xi; Sun, Jia-Lin; Gong, Zhong-Cheng; Lin, Zhao-Quan; Liu, Hui
Abstract: Background: A variety of studies have evaluated the correlation between glucose transporter-1 (GLUT-1) expression and prognosis of oral squamous cell carcinoma (OSCC); however, the results were inconsistent and inconclusive. A meta-analysis was performed to assess the prognostic significance of GLUT-1 in OSCC. Methods: Electronic databases of PubMed, Embase, and Web of Science were searched for relevant studies. The last search was updated on July 2016. Odds ratio (OR) and 95% confidence interval (CI) were pooled to evaluate the relationship between GLUT-1 and clinical features and hazard ratio (HR) and 95% CI were combined to measure the effect of GLUT-1 on overall survival (OS). P value < 0.05 was considered as statistically significant. Results: A total of 13 studies with 1301 subjects were included for meta-analysis. The pooled data showed that high GLUT-1 expression was associated with advanced tumor stages (n = 7, OR = 2.99, 95% CI: 2.01–4.46, P  < 0.001), higher tumor grade (n = 5, OR = 3.34, 95%CI: 1.12–9.94, P  = 0.031), tumor size (n = 5, OR = 3.36, 95%CI: 2.04–5.51, P  < 0.001), lymph node metastasis (n = 5, OR = 3.15, 95%CI: 1.89–5.25, P  < 0.001), tobacco use (n = 3, OR = 2.18, 95%CI: 1.18–4.01, P  = 0.013), and distant metastasis (n = 2, OR = 3.06, 95%CI: 1.19–7.9, P  = 0.02). Furthermore, increased GLUT-1 expression was also correlated with shorter OS (n = 8, HR = 1.88, 95%CI: 1.51–2.33, P  < 0.001). No significant publication bias was detected in this meta-analysis. Conclusion: GLUT-1 overexpression was in connection with aggressive clinical features and worse OS in OSCC. However, further studies are still needed to verify whether GLUT-1 could serve as a prognostic biomarker for OSCC.